2017
DOI: 10.1038/s41598-017-03646-4
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene triggers desensitization of β2-adrenergic pathway

Abstract: Exposure to environmental polycyclic aromatic hydrocarbons (PAHs), such as benzo(a)pyrene (B(a)P), has been linked to several health-threatening risks. PAHs were also shown to hinder adrenergic receptor (ADR) responses. As we previously demonstrated that B(a)P can directly interact with the β2ADR, we investigated here whether B(a)P could decrease β2ADR responsiveness by triggering receptor desensitization phenomena. We firstly showed that exposure to B(a)P reduced β2ADR-mediated epinephrine-induced induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…3). In line with our (Mayati et al, 2017), this indicates that lipophilic organic chemicals extracted by the two least polar solvents interacts with and desensitizes βARs. In contrast, the hydrophilic extracts had no significant effects.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…3). In line with our (Mayati et al, 2017), this indicates that lipophilic organic chemicals extracted by the two least polar solvents interacts with and desensitizes βARs. In contrast, the hydrophilic extracts had no significant effects.…”
Section: Resultssupporting
confidence: 89%
“…Acknowledging that these lipophilic DEP-EOM affect multiple mechanisms, it is tempting to speculate that DCM-EOM activates ROCE via the GPCRs βAR and PAR-2. Studies indicating that certain PAHs may act as βAR agonists and that DEP increase [Ca 2+ ]i via PAR-2 in human bronchial cells, lend support to this suggestion (Li et al, 2011;Mayati et al, 2014;Mayati et al, 2012b;Mayati et al, 2017). However, as we have previously observed that DCM-EOM increased [Ca 2+ ]i via AhR-dependent mechanisms, the possibility that GPCRs could be trans-activated downstream of AhR activation also needs to be considered.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
See 1 more Smart Citation
“…The β 2 AR is extensively expressed in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT different system (respiratory, nervous, cardiovascular, inflammation and immune systems), and promote various physiological functions (bronchodilation, regulation of vasodilation and cardiac muscle contractility, regulation of activities of both T and B lymphocytes, homeostatic and neuroprotective functions, lipolysis regulation) [28,29,[34][35][36][37][38][39][40]. Hence, the observation that B[a]P at low concentrations can bind and stimulate β 2 AR signaling and attenuate effects from epinephrine [19,8,18] is potentially of considerable toxicological importance. As shown in Table 1, interference with GPCRs is not restricted to PAHs and β-adrenoceptors, but other GPCR-targets affected by other EDs are emerging.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with Ca 2+ signaling could therefore lead to endothelial dysfunction [17]. Recent findings also indicate that B[a]P may promote β 2 ARdesensitization by stimulating receptor endocytosis, thus attenuating responses induced by epinephrine [18]. Furthermore, a study on adipocytes suggests that B[a]P disturbs epinephrine signaling through all the three β-adrenoceptors [19], underscoring that adrenoceptor disruption is not limited to interference of β 2 AR function.…”
Section: Complexity Of Gpcr Regulationmentioning
confidence: 99%